Some Hermeneutic Qualities of a Capabilities Approach - Joshua R Markle (University of Calgary, 2019)
This paper draws inspiration from two seemingly disparate cases – one of friendship and one of imagination – to explore some of the hermeneutic qualities of a capabilities approach.